A SEC61A1 variant is associated with autosomal dominant polycystic liver disease. (20th December 2022) - Schlevogt, Bernhard; Schlieper, Vincent; Krader, Jana; Schröter, Rita; Wagner, Thomas; Weiand, Matthias; Zibert, Andree; Schmidt, Hartmut H.; Bergmann, Carsten; Nedvetsky, Pavel I.; Krahn, Michael P.
Abstract: Background and Aims: Autosomal dominant polycystic liver and kidney disease is a spectrum of hereditary diseases, which display disturbed function of primary cilia leading to cyst formation. In autosomal dominant polycystic kidney disease a genetic cause can be determined in almost all cases. However, in isolated polycystic liver disease (PLD) about half of all cases remain genetically unsolved, suggesting more, so far unidentified genes to be implicated in this disease. Methods: Customized next‐generation sequencing was used to identify the underlying pathogenesis in two related patients with PLD. A variant identified in SEC61A1 was further analysed in immortalized patients' urine sediment cells and in an epithelial cell model. Results: In both patients, a heterozygous missense change (c.706C>T/p.Arg236Cys) was found in SEC61A1, which encodes for a subunit of the translocation machinery of protein biosynthesis at the endoplasmic reticulum (ER). While kidney disease is absent in the proposita, her mother displays an atypical polycystic kidney phenotype with severe renal failure. In immortalized urine sediment cells, mutant SEC61A1 is expressed at reduced levels, resulting in decreased levels of polycystin‐2 (PC2). In an epithelial cell culture model, we found the proteasomal degradation of mutant SEC61A1 to be increased, whereas its localization to the ER is not affected. Conclusions: Our data expand the allelic and clinical spectrum for SEC61A1, adding PLD as a new and the major phenotypic trait in the family described. We further demonstrate that mutant SEC61A1 results in enhanced proteasomal degradation and impaired biosynthesis of PC2.